DPYD-guided fluoropyrimidine dose adjustment in colorectal cancer DPYD carriers: start slower to finish stronger - Rosas-Alonso, Rocío; Salas, Nuria Rodríguez; Wert, Pablo Perez; Hoyo, Angela; Martin-López, Susana; Martínez-Pérez, Daniel; Ruiz-Gutiérrez, Iciar; Jiménez-Bou, Diego; Peña, Jesús; Arias, Pedro; Custodio, Ana; Losantos-García, Itsaso; et al. (Frontiers in Pharmacology, 2025)
IntroductionFluoropyrimidines (FP) are the mainstay of colorectal cancer (CRC) treatment, but can cause severe toxicity in up to 40% of patients. Variants in the DPYD gene are associated with these adverse events. A DPYD-guide dose adjustment is now recommended in Europe. This ambispective study aims to analyze the FP-related severe toxicity and the FP dose adjustment in heterozygous DPYD variant carriers with colorectal cancer, comparing a DPYD-guided FP dose adjustment (DA) approach to the non-DPYD-guided FP dose adjustment (NDA).Methods1.279 DPYD genotyping reports were issued. Sixty patients were identified with DPYD variants. Twenty-five CRC patients (17 in the DA cohort and 8 in the NDA cohort) were included in the analysis. Thirty-five patients were excluded from the analysis because they did not satisfy any of the study’s inclusion criteria. Reasons for exclusion included having a diagnosis other than colorectal cancer, not receiving fluoropyrimidine treatment, participation in a clinical trial, or insufficient follow-up.ResultsOf the twenty-five patients included, sixteen patients (94%) started with a 50% FP dose reduction in the DA cohort while 7 out of 8 patients (87%) in the NDA cohort received 100% of dose in cycle 1. In the DA cohort, 12% of patients experienced severe fluoropyrimidines-related adverse events, compared to 50% in the NDA cohort (OR = 0.13; 95%CI: 0.01–0.93; p = 0.05). FP discontinuation due to severe toxicity occurred in 6% of patients in the DA cohort versus 50% in the NDA cohort (OR = 0.06; 95%CI: 0.003–0.55, p = 0.02).DiscussionThese findings suggest that DPYD-guided dose adjustment significantly reduces both the incidence of severe toxicity and the rate of treatment discontinuation in CRC patients. Initiating treatment with a 50% FP reduction allows for dose escalation in patients who exhibit good tolerance and avoid the discontinuation for those patients intolerant to higher doses thereby improving overall treatment adherence and completion.